Role of International Advocacy Groups to Nigeria’s INEC Capacity Building - Gar, Ruqayya, Aminu; Ahmad, Umar Salisu; Umar, Mohammed, Nuru (My University, 2022)
International advocacy groups such as DFID, CIDA, EU, UNDP, USAID and IFES are considered external actors of national development process. Reports on international advocacy groups exist but are limited to academic orientation. This paper focus on the role of these international advocacy groups on Nigeria’s INEC capacity building through a qualitative method of data collection and analysis. Findings conclude that the contributions of these organizations have differed both in their approaches and so is the kind of assistance they rendered to Nigeria’s electoral process since inception of the new democratic transition in 1999. They organised programmes on capacity building for INEC staff, and civic education programmes for the electorates, they enhanced political participation by women, youths and other marginalized groups; improved democratic quality of political commitment; strengthened channels of civic engagement; and promoted credible, transparent and sustainable elections. They also provide funding/ grant sponsorship of pre-election and post-election workshops for accredited observers and training for security officials. This is indeed significant to the prospect’s democratic development, and individual well-being of the citizenry which these international advocacy groups and norms advocate.
Keywords: Advocacy Groups; Capacity building; Democracy; International; Nigeria